Qualitative analysis of major constituents from Xue Fu Zhu Yu Decoction using ultra high performance liquid chromatography with hybrid ion trap time‐of‐flight mass spectrometry. Issue 17 (6th September 2016) - Fu, Chunyan; Xia, Zian; Liu, Yonghui; Lu, Hongmei; Zhang, Zhimin; Wang, Yang; Fan, Xiaqiong
Abstract : Xue Fu Zhu Yu Decoction, a famous formula that has been used for treating many blood stasis‐caused diseases for many centuries, comprises 11 kinds of traditional Chinese medicines. A convenient, efficient, and rapid analytical method was developed to simultaneously determine the major compounds in this decoction. An ultra‐high performance liquid chromatography with hybrid ion trap time‐of‐flight mass spectrometry method was used to rapidly separate and detect the major constituents of the decoction. Using this technique, we identified or tentatively identified 34 compounds, including 21 flavonoids, 5 terpenoids, 3 organic acids, 2 lactones, 1 alkaloid, 1 amino acid, and 1 cyanogenic glycoside. The MS analysis of these constituents was described in detail. Findings may contribute to future metabolic and pharmacokinetic studies of this medicine.